Regulate, replicate, and resist – The conjunctural geographies of platform urbanism - Graham, M (Taylor and Francis, 2020)
Cities are inherently digital. Digital infrastructures that augment the city - the code – the content – fundamentally shape urban life. Many of those digital augmentations of the city have now become part of the ‘platform economy’. Platforms in the urban environment are reshaping urban geographies in fundamentally unaccountable ways. They present themselves as too big to control, too new to regulate, and too innovative to stifle, and remain un-democratic, and usually distant, organizations with no interest in promoting local voices or investing in local priorities. This paper argues that platforms are able to control urban interactions whilst remaining unaccountable through a strategic deployment of ‘conjunctural geographies’ – a way of being simultaneously embedded and disembedded from the space-times they mediate. These conjunctural geographies, however, render platforms vulnerable. The ephemeral nature of platforms means we can avoid them, circumvent them and replicate them; their material nature suggests points of regulation and resistance. As such, the paper closes by pointing to three broad strategies —regulate, replicate, and resist - which can be deployed to build alternate platform futures. Each of which is built on understanding the simultaneously embedded and disembedded ways in which platforms occupy their conjunctural geographies.